Characterization and multiplexing of 21 microsatellite markers for the herb Noccaea caerulescens (Brassicaceae)1. (9th December 2015) - Mousset, Mathilde; Flaven, Elodie; Justy, Fabienne; Pouzadoux, Juliette; Gode, Cécile; Pauwels, Maxime; Gonneau, Cédric
Abstract : Premise of the study: Multiplexed microsatellite markers were developed for population genetic studies in the pseudometallophyte Noccaea caerulescens (Brassicaceae), a model species to investigate metal tolerance and hyperaccumulation in higher plants. Methods and Results: Microsatellite loci were isolated through pyrosequencing of an enriched DNA library. Three multiplexes combining four previously published and 17 newly designed markers were developed. The new markers were screened in metallicolous and nonmetallicolous populations from southern France. The total number of alleles per locus ranged from five to 18. The observed heterozygosity per locus and per population ranged from 0 to 0.83, and expected heterozygosity ranged from 0 to 0.89. Conclusions: The investigated loci showed reasonable to high levels of polymorphism at the regional scale. The multiplex set should be helpful in investigating genetic diversity, population structure, and demographic history in N. caerulescens at various spatial scales.